For a historiography of the Alagoas working class - Farias, Ivo dos Santos [UNESP] (Pontificia Univ Catolica Minas Gerais, 2018)
The following article seeks to present an overview about the historiographical construction of alagoan workers, between the late 1990s and the presente day. To do this, it indicates the academic production of three different generations of scholars, as well as the profile of each of them, signaling advances in research and continuities between generations. In addition, it discusses numbers that identify significant production growth in this area, comparing it with other regions on the workforce in Alagoas. Finally, it understands that these studies have contributed to demystify a present perspective still in the collective imaginary that Alagoas understands only a historically constructed space on the large latifudio, since in that it points to the existence of factory experiences and political trajectories connected with the process of modernization throughout the 20th century.
Keywords: Historiography; Working class; Alagoas